(untitled) (Perner’s Contacts, 2018)
The river Vah is the longest Slovak river, which occupies up to one third of Slovakia with its catchment area. Its importance lies not only in the production of electricity but also as a transport route that would help to develop the economy especially in the northwest and southern parts of Slovakia. The basic goal of the project Vah waterway is to make the Vah river navigable from Komarno to Zilina. With some limitations commercial navigation only carries out on its lower stretch. It is necessary to reconstruct or build lifting devices and canals on its middle or upper part.